The Effect of Calibration on Caries Risk Assessment Performance by Students and Clinical Faculty. Issue 6 (1st June 2017) - Young, Douglas A.; Alvear Fa, Bernadette; Rogers, Nicholas; Rechmann, Peter
Abstract : Caries management requires a complete oral examination and an accurate caries risk assessment (CRA). Performing Caries Management by Risk Assessment (CAMBRA) is inefficient when the caries risk level assignment is incorrect. The aim of this study was to evaluate the ability of faculty members and students at one U.S. dental school to correctly assign caries risk levels for 22 CRA cases, followed by calibration with guidelines on how to use the CRA form and a post‐calibration test two months after calibration. Inter‐examiner reliability to a gold standard (consensus of three experts) was assessed as poor, fair, moderate, good, and very good. Of the 162 students and 125 faculty members invited to participate, 13 students and 20 faculty members returned pre‐calibration tests, for response rates of 8% and 16%, respectively. On the post‐calibration test, eight students and 13 faculty members participated for response rates of 5% and 10%, respectively. Without guidelines and calibration, both faculty members and students when evaluated as one group performed only poor to fair in assigning correct caries risk levels. After calibration, levels improved to good and very good agreements with the gold standard. When faculty and students were evaluated separately, in the pre‐calibration test they correctly assigned the caries risk level on average in only one‐quarter of the cases (students 24.1%±13.3%; faculty 23.6%±17.5%). After calibration, both groups significantly improved their correct assignment rate. Faculty members (73.8% correct assignments) showed even significantly higher correct assignment rates than students (47.7% correct assignments). These findings suggest that calibration with a specific set of guidelines improved CRA outcomes for both the faculty members and students. Improved guidelines on how to use a CRA form should lead to improved caries risk assessment and proper treatment strategy for patients.